THE INFLUENCE OF PRODUCT QUALITY AND PRICE ON CUSTOMER SATISFACTION AT SHOPATALEEN FASHION BRAND - Reza Azkia Rahmi; Maya Ariyanti (Jurnal Ilmiah MEA (Manajemen, Ekonomi, & Akuntansi), 2022)
Growth in the GDP demonstrates that one of the most important segments of Indonesia's emerging creative industry is fashion. Fashion contributed 18.15 percent, or 166 trillion. According to these statistics, one of Indonesia's creative sectors that contributes significantly is fashion. In terms of fashion, life in Bandung has its own conveniences. Of course, many individuals in Bandung are content with regional manufacturers, among them the Shopataleen Fashion Brand. The purpose of this study is to ascertain the relationship between product quality and pricing and customer satisfaction at the Shopataleen Fashion Brand as well as to identify the factors that have the greatest impact on customer satisfaction. By distributing questionnaires with a Likert scale, primary data were collected for this study and 100 persons responded to the survey. SPSS was employed as the data analysis method in this study (Statistical Program for Science). This study demonstrates that there is a simultaneous influence between Product Quality and Price on Customer Satisfaction at the Fashion Shopataleen Brand by 58%, with the remaining 42% being influenced by other variables outside the study's regression model, based on the results of questionnaires and data processing analysis.